2008
DOI: 10.1002/chem.200701613
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolar Dihydrogen Bonds—On a Gliding Scale from Weak Dihydrogen Interaction to Covalent HH in Symmetric Radical Cations [HnE‐H‐H‐EHn]+

Abstract: The electronic structures and bonding patterns for a new class of radical cations, [HnE-H-H-EHn]+ (EHn=element hydride, E=element of Groups 15-18), have been investigated by applying quantum-chemical methods. All structures investigated give rise to symmetric potential energy minimum structures. We envisage clear periodic trends. The H--H bond length is shorter for elements toward the bottom of the periodic table of elements, and a short H--H bond corresponds to accumulation of electron density in the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…for the C−F⋅⋅⋅F−C interaction, which was responsible for the integrity of a self‐assembled 2D supramolecular architecture using fully fluorinated compounds . The Δ E values of comparable magnitude have been reported for other non‐covalent interactions …”
Section: Resultssupporting
confidence: 58%
“…for the C−F⋅⋅⋅F−C interaction, which was responsible for the integrity of a self‐assembled 2D supramolecular architecture using fully fluorinated compounds . The Δ E values of comparable magnitude have been reported for other non‐covalent interactions …”
Section: Resultssupporting
confidence: 58%
“…Further Valence Bond studies have revealed [78], in line with our conclusions, that, apart from the crucial dispersion term, also the σ/σ*(C-H) polarization/charge transfer and electrostatic contributions are important. Recently, numerous reports are present in the literature on the stabilizing nature of CH¨¨¨HC interactions in various types of hydrocarbons [37,38,[79][80][81][82][83][84][85], as well as their importance in catalysis [42,43,86].…”
Section: Resultsmentioning
confidence: 99%
“…The calculated dissociation energy of this ion is about 0.21 eV 9. The existence of a long-lived, electronically excited He 2 H 2 + ion with centrosymmetric structure, [He-H-H-He] + , was proposed by Uggerud and co-workers19 and experimentally identified based on its unusual metastable dissociation into HeH + +neutral fragments 20. To the best of our knowledge, no calculations exist for complexes of H 2 + with more than two helium atoms.…”
Section: Introductionmentioning
confidence: 85%